1998
DOI: 10.1038/nm0598-623
|View full text |Cite
|
Sign up to set email alerts
|

Detection of tumor angiogenesis in vivo by αvβ3-targeted magnetic resonance imaging

Abstract: Angiogenesis, the formation of new blood vessels, is a requirement for malignant tumor growth and metastasis. In the absence of angiogenesis, local tumor expansion is suppressed at a few millimeters and cells lack routes for distant hematogenous spread. Clinical studies have demonstrated that the degree of angiogenesis is correlated with the malignant potential of several cancers, including breast cancer and malignant melanoma. Moreover, the expression of a specific angiogenesis marker, the endothelial integri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
492
1
5

Year Published

1999
1999
2011
2011

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 833 publications
(505 citation statements)
references
References 13 publications
7
492
1
5
Order By: Relevance
“…The criterion is that the signal be greater than or equal to three times the standard deviation (σ) of the noise level [26,27]. This criterion results in the following condition: [4] where N is the magnitude of the signal in the region of interest of the MR images. [5] where C Gd (M) is the concentration of GdDO3A-FLAG in TBS buffer or on the anti-FLAG® M2-agarose affinity gel layer as determined by ICP-MS, N Gd is the MR signal intensity after addition of GdDO3A-FLAG, N 0 is the MR signal intensity without addition of GdDO3A-FLAG, and the standard deviation (σ) was determined from the signal intensity without addition of GdDO3A-FLAG.…”
Section: Detection Limits (Dl) In Solutions and Gelsmentioning
confidence: 99%
See 1 more Smart Citation
“…The criterion is that the signal be greater than or equal to three times the standard deviation (σ) of the noise level [26,27]. This criterion results in the following condition: [4] where N is the magnitude of the signal in the region of interest of the MR images. [5] where C Gd (M) is the concentration of GdDO3A-FLAG in TBS buffer or on the anti-FLAG® M2-agarose affinity gel layer as determined by ICP-MS, N Gd is the MR signal intensity after addition of GdDO3A-FLAG, N 0 is the MR signal intensity without addition of GdDO3A-FLAG, and the standard deviation (σ) was determined from the signal intensity without addition of GdDO3A-FLAG.…”
Section: Detection Limits (Dl) In Solutions and Gelsmentioning
confidence: 99%
“…There is a great deal of interest in enhancing the utility of these tools in medicine and research through the development of molecularly-targeted MRI contrast agents. One example might be a chimeric molecule comprised of a contrast agent tethered to a molecule capable of binding to a specific protein or other biomolecular target with high affinity and specificity [4][5][6][7][8][9][10][11][12][13][14][15][16][17]. For example, we previously reported that a peptide selected from a phage display library to bind the yeast Gal80 protein can be linked to GdDOTA to create a reagent capable of imaging Gal80 protein in vitro [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, antibodies or peptides capable of blocking the activity of integrin ␣ v ␤ 3 are classified as anti-angiogenic (4 -8). In this vein, several reports suggest that integrin ␣ v ␤ 3 is a target for anti-angiogenic therapy (7)(8)(9)(10). Several growth factors including FGF2 and tumor necrosis factor-␣ increase ␣ v ␤ 3 expression in the developing blood vessels of chick embryo (11) and rabbit cornea (5).…”
mentioning
confidence: 99%
“…Antibody-coated paramagnetic liposomes (35), Gd-perfluorocarbon nanoparticles conjugated to anti-integrin a v h 3 monoclonal antibody (36), and integrin a v h 3 -targeted paramagnetic nanoparticles (37) have been reported for magnetic resonance imaging of integrin a v h 3 expression (Fig. 4A).…”
Section: Non^radionuclide-based Imaging Of Integrinmentioning
confidence: 99%